Optimization of the Ultrasound-Assisted Extraction of Phenolic Antioxidants from Cistus Salvifolius L. Using Response Surface Methodology - Christou, Atalanti; Nikola, Fotini; Goulas, Vlasios (My University, 2024)
The current work aims to optimize the ultrasound-assisted extraction (UAE) of Cistus salviifolius L. (aerial parts) antioxidative phenolic compounds using response surface methodology. A Box-Behnken design has been conducted to investigate the effect of four factors, namely: (i) percentage of ethanol (50-90 %, v/v), (ii) temperature (40-80 °C), (iii) solvent-solid ratio (10-50 mL g-1) and (iv) extraction time (5-25 min) on four responses, namely: total phenolic content (TPC), total flavonoid content (TFC) 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical inhibition, and ferric reducing antioxidant power (FRAP). Based on the desirability index, UAE with 50 % (v/v) ethanol, at 80 °C, using a solvent-solid ratio of 32.24 mL g-1, for 21 min resulted in the maximum recovery of phenolic antioxidants. Under optimum conditions, the experimental values of TPC, TFC, % DPPH radical scavenging activity, and FRAP were 171.67±4.69 mg GAE g-1, 26.87±0.78 mg CE g-1, 81.31±0.16 %, and 1038.22±7.69 μmol TE g-1, respectively. Results shows a reasonable agreement of experimental values with the predicted ones; the absolute error values being in all cases lower than 2.90 %. The present work provide a developed eco-friendly extarction method that is appropriate for the improved recovery of phenolic antioxidants from C. salviifolius L.
Keywords: Antioxidant activity; Extraction; Flavonoid; Phenolic compounds; Recovery